Self-Medication Among King Khalid University Students, Saudi Arabia - Alshahrani SM; Alavudeen SS; Alakhali KM; Al-Worafi YM; Bahamdan AK; Vigneshwaran E (Dove Medical Press, 2019)
Sultan M Alshahrani,1 Sirajudeen Shaik Alavudeen,1 Khaled M Alakhali,1,2 Yaser Mohammed Al-Worafi,3 Ahmed K Bahamdan,1 Easwaran Vigneshwaran1 1Clinical Pharmacy Department, College of Pharmacy, King Khalid University, Abha, Saudi Arabia; 2Clinical Pharmacy Department, College of Pharmacy, USCI University, Kuala Lumpur, Malaysia; 3Clinical Pharmacy Department, College Of Pharmacy, University of Science and Technology of Fujairah, Fujairah, UAECorrespondence: Yaser Mohammed Al-WorafiCollege of Pharmacy, University of Science And Technology of Fujairah, Fujairah, UAETel +971543041178Email yworafi@yahoo.comPurpose: This study objective was to explore the pattern of self-medications among King Khalid University students, Saudi Arabia.Patients and methods: A cross-sectional study was conducted over five months among King Khalid University students, Abha, Saudi Arabia.Results: Among all the study participants, nearly 98.7% were practicing self-medication. Headache (75.9%), cough and cold (52.5%), and fever (35.6%) and body pain (24.6%) were the most reported symptoms. Use of painkillers (91.6%) was significantly predominant among the medical students, whereas non-medical students used antibiotics (35.4%).Time saving (64.2%), mild symptom (51.7%) and quick relief (36.9%) were the reasons behind seeking self-medication in this study.Conclusion: Self-medications was common in King Khalid University. Educational programs are highly recommended.Keywords: self-medication, students, medical, nonmedical, King Khalid University, Saudi Arabia